The effects of atmospheric nitrogen deposition in coral-algal phase shifts on remote coral reefs - Fu, Yichen; Chen, Xiaoyan; Liu, Yuchen; Li, Yuxiao; Yu, Kefu (Frontiers in Marine Science, 2024)
Remote seawater has been considered a potential refuge for corals in the face of anthropogenic disturbances. However, these remote areas may receive increased atmospheric N deposition, and the ecological consequences remain unclear. This field survey revealed coral-algal phase shifts in the mid-north of the South China Sea. These shifts were observed in 44%, 13.6%, and 26.5% of the sampled reef sites at depths of 1-4 m, 5-8 m, and 10-15 m, respectively. Over 50% of sections in the deeper depths hosted fewer corals compared to shallower areas, coinciding with a higher abundance of macroalgae in the deeper layers. Furthermore, based on long-term observation of atmospheric N flux, laboratory experiments were conducted to explore the cause of coral declines. The results indicate that N supply efficiently promoted macroalgae growth. The saturation of N absorption by macroalgae occurred within 2 weeks, leading to nutrient accumulation in seawater, especially nitrate, which had a direct impact on corals. While moderate N fluxes appeared to mitigate coral bleaching, high N fluxes, even with a balanced P supply or medium level of nutrients with an imbalanced N/P ratio, can both increase the susceptibility of corals to heat bleaching. This study explains the coral-algal phase shift in remote and relatively deep seawater and improves understanding of the cause-and-effect relationship between atmospheric N deposition and coral reef decline.